PENGEMBANGAN MODEL PROBLEM BASED LEARNING BERBASIS TEKNOLOGI UNTUK MENINGKATKAN MOTIVASI BELAJAR DAN LITERASI NUMERASI PADA MATA PELAJARAN MATEMATIKA KELAS 6 SD - Samsudin; Puryati; Sumarni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research aims to develop a technology-based Problem Based Learning (PBL) model that is feasible and effective in improving learning motivation and numeracy literacy of 6th grade elementary school students in mathematics. The research method used was Research and Development (R&D) with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The subjects were 34 sixth-grade students of UPTD SD Negeri 2 Taman Negeri, Way Bungur District, East Lampung Regency, selected using cluster random sampling. Research instruments included expert validation sheets, learning motivation questionnaires, numeracy literacy tests (pretest-posttest), observation sheets, and practicality questionnaires. The results showed that the technology-based PBL model developed had very good feasibility based on expert validation with a score of 94.44%. The practicality of the model was in the very practical category with an average score of 3.82 on a scale of 4.00. The effectiveness of the model was demonstrated through an increase in student learning motivation with an average percentage of 85.29% (very high category) and an increase in numeracy literacy with an N-Gain value of 0.7658 (high category). The model integrates digital platforms such as Wordwall and PhET simulations within five technology-based PBL stages. The conclusion is that the technology-based PBL model is proven feasible, practical, and effective in improving learning motivation and numeracy literacy of sixth-grade elementary school students.